2021
DOI: 10.1108/cg-03-2021-0116
|View full text |Cite
|
Sign up to set email alerts
|

External whistleblowing intentions of auditors: a perspective based on stimulus–organism–response theory

Abstract: Purpose This study aims to examine the roles of perceived organisational support (POS), attitude and self-efficacy in understanding the external whistleblowing intentions among senior auditors through the lens of stimulus–organism–response theory. Design/methodology/approach This study uses data from 119 senior auditors in audit firms in Malaysia. POS is predicted to be a stimulus factor from the external environment that affects the attitude and self-efficacy (organism) of the auditors and reassures them to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 80 publications
2
16
1
Order By: Relevance
“…Theory of Planned Behavior (TPB) had become one of the most adopted (or most used) theory or framework which was mainly used by researchers or academicians all around the world across generations to determine which factors or forces could influence or determine both individuals or consumers' intention and decision to purchase or buy certain product. Developed by Ajzen (1985) in order to address all of the weaknesses or shortcomings presented on the previous similar theory developed by Fishbein and Ajzen (1975) (which was named theory of reasoned action or TRA), the basic notion of TPB argue that there are actually 3 (three) major forces or factors which could influence consumers or individuals' intention (and ultimate decision) to perform certain behavior, in which, these three major forces or factors are consumers' attitude toward the behavior, subjective norm, and perceived behavioral control (PBC) (Tweneboah-Koduah et al, 2022;Masrizal et al, 2022;Mansor et al, 2022;Batool et al, 2022;Arkorful and Hilton, 2022;Wilson & Edelyn, 2022).…”
Section: Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%
“…Theory of Planned Behavior (TPB) had become one of the most adopted (or most used) theory or framework which was mainly used by researchers or academicians all around the world across generations to determine which factors or forces could influence or determine both individuals or consumers' intention and decision to purchase or buy certain product. Developed by Ajzen (1985) in order to address all of the weaknesses or shortcomings presented on the previous similar theory developed by Fishbein and Ajzen (1975) (which was named theory of reasoned action or TRA), the basic notion of TPB argue that there are actually 3 (three) major forces or factors which could influence consumers or individuals' intention (and ultimate decision) to perform certain behavior, in which, these three major forces or factors are consumers' attitude toward the behavior, subjective norm, and perceived behavioral control (PBC) (Tweneboah-Koduah et al, 2022;Masrizal et al, 2022;Mansor et al, 2022;Batool et al, 2022;Arkorful and Hilton, 2022;Wilson & Edelyn, 2022).…”
Section: Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%
“…More relevant to the present study are the perspectives involving WBIs by professional accountants. Aside from the commonly-used theory of planned behaviour (Ajzen, 1991), there are various theories incorporated in whistleblowing models involving professional accountants and auditors that are mostly found to be concentrated either on individual or organisational factors (Tuan Mansor et al, 2021b). Among these are justice theory (Rawls, 1971), institutional theory (DiMaggio and Powell, 1983), principled organisational dissent (Graham, 1986), independence commitment (Gendron et al, 2006), and organisational support theory (Eisenberger et al, 1986).…”
Section: Models and Determinants Of Whistleblowingmentioning
confidence: 99%
“…Latan et al, (2019) extend the fraud triangle model that consists of pressure or financial incentives, opportunity, and rationalisation in the whistleblowing context in Indonesia. In Tuan Mansor et al (2021b), the stimulus-organism-response theory of Mehrabian and Russell (1974) is introduced to understand how the environment in an audit firm affects the reaction of whistleblowers, which will then result in a whistleblowing decision. In the institutional setting of Kenya, Hellman et al, (2021) apply the construct of ethnic identity (Phinney, 1992) and construal of self (Markus and Kitayama, 1991) in extrapolating WBIs among auditors.…”
Section: Models and Determinants Of Whistleblowingmentioning
confidence: 99%
“…Palmer et al (2004) outlined that accountants with a strong commitment to their profession tend to possess a strong moral need to engage in behaviours that benefit the profession, such as reporting others' questionable activities. Tuan Mansor et al (2021) revealed that auditors' willingness to act ethically is highly influenced by their professional dedication.…”
Section: Audit Profession Factormentioning
confidence: 99%
“…Tuan Mansor et al (2021) mentioned that partners of the Big 4 audit firms tend to demand correction of amount misstatements on the face of the financial statements than those disclosed in the notes of the financial statements (Tuan Mansor et al, 2021). Kaawaase et al (2016) stated that the inability to notice and disclose a violation of obligatory accounting rules, such as disclosures indicates degraded audit quality.…”
Section: Audit Procedures In Digital Auditmentioning
confidence: 99%